Injection practices among the diabetes patients on insulin therapy in Chitradurga - Sindhu, B. M.; Rashmi, B. M.; Prashanth, G.; Gowda, M. R. Nagendra (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes mellitus has emerged as a global health problem. Insulin is the essential treatment modality for significant number of diabetic patients. Nearly 4 out of 10 patients with T2DM in India are using insulin, either alone or in combination with oral hypoglycemic drugs (OADs). The present study was conducted with the objectives to assess the knowledge and insulin injection practices, risk factors of sharps injury among diabetic patients who are on insulin treatment. Methods: Cross sectional study was conducted at a Basaveshwara hospital, Chitradurga, among diabetic patients on insulin treatment for minimum of past 6 months. Insulin injection technique questionnaire (ITQ) was administered to study participants and proforma was filled by interview technique. Results: 100 patients participated in the study. Syringe and needle device and 6 mm needle are most commonly used devices. 5-10 seconds was the most common duration of time (54%) for which the patients continued to keep the needle inserted in injection site after insulin injection. A 26% patients had lip hypertrophy at injection sites. Among households of the insulin users, a high percentage of children (41%) and house keeper/waste collectors (32%) were at risk of sharps injury. A majority of 55% of the insulin users reported that they didn’t have appropriate disposal containers for the used sharps. Conclusions: A 29% of participants did not practice proper rotation of injection site. Reuse of insulin needles was common practice. Pain/tenderness, lipo-hypertrophy and leakage of insulin after injection were noted at injection site. 10 seconds dwell time was reportedly practiced by only 23%, about half of patients skipped insulin injections and didn’t follow appropriate disposal of used sharps, thereby exposing both family members and waste collectors/handlers to higher risks of sharps injuries.